INSTITUTIONAL NETWORK STRUCTURE IN CITARUM WATERSHED MANAGEMENT - Rudi Saprudin Darwis; Risna Resnawati; Eva Nuriyah Hidayat (Universitas Padjadjaran, 2022)
To overcome the pollution of the Citarum River, a comprehensive environmental management effort is needed and integrates various programs or activities from various parties. This study will describe the structure of the institutional network among the institutions involved in the management of the Citarum watershed. The aspects studied are the elements of the institution that enable the institution to develop properly and the aspects contained in the institutional network, namely the actors involved, distribution of resources, opportunities for exchange, exchange relations, and network structure. The research was conducted in the Citarum watershed area in Sector 7, Bandung Regency, namely in Baleendah District. Data were collected from institutions identified as institutions involved in the management of the Citarum watershed. The results showed that apart from the Sector 7 Commander, the institutions involved in the management of the Citarum watershed consisted of local/regional non-governmental organizations (NGOs), government agencies, local governments, academics, and the community. Each stakeholder plays a role in accordance with his position and limits of authority and through involvement by the Sector Commander (Dansector) 7 who plays the role of coordinator and is quite dominant in coordinating Citarum watershed management activities. In order for the achievements of this program to be sustainable, this dominance must be balanced with strengthening community capacity to avoid dependence on central government programs.